2021
DOI: 10.3390/agronomy11112292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seed Dormancy, One of the Key Domestication Traits in Chickpea

Abstract: Legume seed dormancy has been altered during the domestication process, resulting in non-dormant seeds with a testa that is readily permeable for water. Ultimately, this provides fast and uniform germination, in contrast to dormant seeds of the wild progenitor. To date, germination and seed dormancy were studied mostly in relation to two types of cultivated chickpea: kabuli and desi. We studied seed dormancy, from physiological and anatomical perspectives, in chickpea crops and compared cultivated chickpeas to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The kabuli type produces comparatively larger and smoother round seeds with thinner unpigmented seed coats; the seed coat forms approximately 5% of the total weight of the seed [ 1 , 2 ]. The larger-seeded kabuli type was likely derived from the smaller-seeded desi type [ 3 , 4 ], while seeds of the desi type are very similar to the seeds of the ancestor of cultivated chickpea, C. reticulatum Ladiz. [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kabuli type produces comparatively larger and smoother round seeds with thinner unpigmented seed coats; the seed coat forms approximately 5% of the total weight of the seed [ 1 , 2 ]. The larger-seeded kabuli type was likely derived from the smaller-seeded desi type [ 3 , 4 ], while seeds of the desi type are very similar to the seeds of the ancestor of cultivated chickpea, C. reticulatum Ladiz. [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed that dormancy is not directly related to the thickness of the seed coat in chickpea [ 4 ], and it is more likely to be mediated by the chemical composition of the seed coat. Here, we aim to take our investigation of dormancy a step further by analyzing the relative concentration of selected phenolic acids and flavonoids in the seed coats of wild and cultivated genotypes and derived recombinant inbred lines of the chickpea.…”
Section: Introductionmentioning
confidence: 99%
“…Further genetic analysis will be aided by recently reported transcripts associated with seed coat formation in V. villosa ( Ali et al., 2023 ). Prior reports of legume seed dormancy reduction during domestication are through mutations that weaken the seed coat ( Smýkal et al., 2014 ; Sun et al., 2015 ; Chai et al., 2016 ; Sedláková et al., 2021 ; Soltani et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting germination and seed dormancy patterns have extensively been reported in chickpea (Cicer arietinum) by Sedlakova et al (2021). In groundnut seed dormancy, which causes huge economic losses due to in situ sprouting at times in Spanish-type varieties (Fig.…”
Section: 3mentioning
confidence: 97%